Perception of Tradional Fisherman Community Tarek Pukat towards the Effort of to Preserve of Local Wisdom to the Sea Coastal conservation in Gampong Jawa - Maryam Maryam; Asriani Asriani; Erdi Surya; Anita Noviyanti; Muhammad Ridhwan; Armi Armi; Muchsin Muchsin (International Conference on Multidisciplinary Research, 2022)
Perception is the experience of an object, phenomenon, or connection obtained by inferring information and interpreting a message. The perceptions of individuals can be very different even if the objects we observe are the same. This research is about the perception of the traditional fishing community of Tarek Pukat which aims to find out the efforts made by the traditional fishing community of Tarek Pukat to preserve the local wisdom of marine coastal conservation in Gampong Jawa. In this study, a sample was selected by 12 traditional fishermen of Tarek Pukat while the instrument consisted of questionnaires and interview guidelines. The results of the data collection found that the perception of traditional fishing communities of Tarek Pukat towards local wisdom efforts for marine coastal conservation, generally fishermen showed positive perceptions. It can be seen from the answer to questionnaires and interviews that fishermen have understood the meaning of local wisdom and how local wisdom includes in daily habits by doing an activity such as clean of the coastal areas through social works, prohibited to throw trash on the sea related to the marine life preservation. Fishermen also understand the forbidden day of Tarek Pukat, which is on Friday and the day of religion commemorates and the Independence Day celebration. The other understanding that fishermen reflect about local wisdom is not to cut the trees of Aron which planting along the coast. It caused fish on the sea difficult to breed. Apart from that, the system of Tarek Pukat that fishermen do by local wisdom, still observes the coastal mouth areas in order to obtain the quality of the fish that they catch. Keywords: Perception, Tradional Fisherman, Tarek Pukat, Local Wisdom.